2014
DOI: 10.1080/09644016.2014.973222
|View full text |Cite
|
Sign up to set email alerts
|

Party differences and energy reform: fiscal conservatism in the California legislature

Abstract: Research building on political economy and ecological modernisation theories has paid increasing attention to the conditions that affect the prospects for environmental reform. Much work focuses on variation among political units in support of a single type of energy policy, whereas we examine within-state variation in support of a wide range of energy reform policies. Applying multilevel analyses to the 2011-2012 legislative session in California, we identify bill characteristics associated with divisions bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Thus, we added another hypothesis about additional categories of laws that support REEE but do not support a particular type of technology or policy instrument. Because conservatives are concerned with reducing regulatory burdens on households and businesses, we reason that the reduction of regulations may receive relatively higher levels of support than REEPS laws [20]. Likewise, bills that merely authorize a local government entity to engage in an activity (such as providing licenses for solar contractors) would not involve government spending or interventions in the private sector and therefore might receive higher levels of support in comparison with REEPS laws.…”
Section: Hypothesismentioning
confidence: 97%
See 3 more Smart Citations
“…Thus, we added another hypothesis about additional categories of laws that support REEE but do not support a particular type of technology or policy instrument. Because conservatives are concerned with reducing regulatory burdens on households and businesses, we reason that the reduction of regulations may receive relatively higher levels of support than REEPS laws [20]. Likewise, bills that merely authorize a local government entity to engage in an activity (such as providing licenses for solar contractors) would not involve government spending or interventions in the private sector and therefore might receive higher levels of support in comparison with REEPS laws.…”
Section: Hypothesismentioning
confidence: 97%
“…Instead, we are interested in how policy design distinctions are related to meaningful ideological distinctions that in turn inform how legislators view, evaluate, and support different types of REEE policy. Recent research has shown that political differences over environmental policy vary across issue type and may fluctuate over time [19], and in a study of the California legislature it was shown that differences between types of green-energy laws are related to ideological differences [20]. However, to date no research has explored the connection between ideology and REEE policy type in a systematic way across a broad range of REEE policies.…”
Section: Theoretical Backgroundmentioning
confidence: 98%
See 2 more Smart Citations
“…Some approaches focus on how institutions, including laws and treaties, shape the actions of individuals, organizations and nations (9,(12)(13)(14)(15). Others emphasize the dynamics of political power (6)(7)(8)(16)(17)(18)(19)(20). As Shwom argues, who has power influences what polices, programs, and institutions are in place to moderate or exacerbate how human actions influence the environmentpolitical factors are part of what are commonly called the driving forces of environmental change (21).…”
mentioning
confidence: 99%